Corporate leverage and growth: a general equilibrium analysis - Dilip K., Ghosh (Universiti Utara Malaysia, 2003)
Within the framework of general equilibrium in which there are two corporations generating net earnings by efficient utilization of debt and equity capital it is demonstrated that optimum capital structure indeed exists for each firm and for the economy in competitive capital market. Since the result is strikingly different from the celebrated proposition on capital structure, an attempt is made to compare this analytical model with the classic paradigm of Modigliani and Miller: The efects of resource allocation are also examined and the existing thoughts on leverage are brought out in this work that subsumes growth and capital accumulation.